The Role of Financial Technology (Fintech) in ZIS Management to Overcome Poverty - A. Zuliansyah; Dimas Pratomo; Okta Supriyaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Indonesia's zakāh‎ potential is large enough to overcome poverty, but the Indonesian population living below the poverty line is still quite high, reaching 25.95 million people. These data indicate that the large potential of zakāh‎ has not contributed enough to poverty alleviation in Indonesia. To increase zakāh‎ collection, the Zakāh‎ Management Organization (OPZ) innovates by using fintech in its management. The study aims to see how the role of fintech in managing ZIS is to contribute to poverty alleviation in Indonesia. The method used is a qualitative method by analyzing data and facts obtained from the object under study namely; BAZNAS Central Jakarta and BAZNAS Prov. DIY 2020 descriptively and in detail. The results of the study indicate that fintech has played a significant role in increasing zakāh‎ collection over the last five years. It can be seen from the growth of zakāh‎ distribution from 2015 to 2019 experienced a significant increase, reaching an average of 40.93%.